Poisoning - From Specific Toxic Agents to Novel Rapid and Simplified Techniques for Analysis 2017
DOI: 10.5772/intechopen.72004
|View full text |Cite
|
Sign up to set email alerts
|

Acute Poisoning with Neonicotinoid Insecticide

Abstract: Neonicotinoids are a class of insecticides considered less toxic to humans than organophosphates, carbamates, organochloride and pyrethroids. The purpose of this chapter was to systematize existing data in the literature on acute intoxication with neonicotinoids to help practitioners. Clinical manifestations vary across diferent human systems.Gastrointestinal symptoms consist of nausea, vomiting, abdominal pain and corrosive lesions. In the central nervous system, headaches, agitation, confusion, fasciculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…30, 12 and 6 mg AI/kg b.w., for subacute 28days repeated dose toxicity study. Th e clinical symptoms of TMX observed, in the acute toxicity study, were mostly distinguished within the fi rst 3 h of exposure to high doses of TMX and this is reliable with the known mode of action for neonicotinoids that target Nicotinic Acetylcholine receptor (nAChR) of the postsynaptic membranes from both nerve and muscle cells and thus disrupt the transmission of the nervous infl ux into the central and peripheral nervous system [53]. Th e most observed toxicity signs of TMX reported within the fi rst 2-3 h of administration of TMX included vomiting, nausea, agitation and multiple episodes of generalized tonic-clonic seizures [54].…”
Section: Discussionsupporting
confidence: 53%
“…30, 12 and 6 mg AI/kg b.w., for subacute 28days repeated dose toxicity study. Th e clinical symptoms of TMX observed, in the acute toxicity study, were mostly distinguished within the fi rst 3 h of exposure to high doses of TMX and this is reliable with the known mode of action for neonicotinoids that target Nicotinic Acetylcholine receptor (nAChR) of the postsynaptic membranes from both nerve and muscle cells and thus disrupt the transmission of the nervous infl ux into the central and peripheral nervous system [53]. Th e most observed toxicity signs of TMX reported within the fi rst 2-3 h of administration of TMX included vomiting, nausea, agitation and multiple episodes of generalized tonic-clonic seizures [54].…”
Section: Discussionsupporting
confidence: 53%
“…They also made very short visits to flowers, leaving the sprayed area quickly. This kind of behaviour might be due to the neurotoxic effect of the tested insecticide (Fishel, 2005; Nistor et al., 2017; Schmuck, 1999) and should deserve consideration in future studies. Pecenka et al.…”
Section: Discussionmentioning
confidence: 99%
“…They also made very short visits to flowers, leaving the sprayed area quickly. This kind of behaviour might be due to the neurotoxic effect of the tested insecticide (Fishel, 2005;Nistor et al, 2017;Schmuck, 1999) and should deserve consideration in future studies. Pecenka et al (2021) showed that insecticide applications can be highly reduced (by 95%) while maintaining or enhancing crop yields through wild pollinator conservation.…”
Section: Effect Of Imidacloprid Spray On Fruit Setmentioning
confidence: 99%
“…It causes various skin ailments like rashes and oedema, headache, ocular irritation and lacrimation, diarrhea, vomiting and chronic exposure may lead to cancer [2][3]. Recently, many researchers have reported that interaction of humans to pesticide for a certain time period cause the severe neurophysiological and neurobehavioral abnormalities [4]. Flonicamid is a pyridine carboxamide insecticide, has 4-trifluoromethylnicotinamide (TFNA-AM) as a major metabolic component.…”
Section: Introductionmentioning
confidence: 99%